Evaluasi Sifat Fisik Tanah Di Lahan Perkebunan Dengan Sistem Pengelolaan Organik Dan Konvesional - Halawa, Silvia Siska; Zebua, Awis Naria (CV. SINAR HOWUHOWU, 2024)
Soil physical properties play a crucial role in supporting the productivity and sustainability of plantation land. However, changes in management systems, both organic and conventional, often have a significant impact on soil physical conditions. Problems faced in conventional plantation land include decreased soil structure quality, increased soil density, and decreased air infiltration capacity, caused by intensive use of chemicals and unsustainable land management. On the other hand, organic management systems are considered capable of improving several soil physical characteristics, such as increased porosity, aggregate stability, and soil ability to retain moisture, in-depth research is still needed to validate these benefits quantitatively. This study aims to compare the effects of the two management systems on soil physical properties, including texture, structure, porosity, density, and air content. Soil samples were taken from organic and conventionally managed plantation lands, and measured using standard laboratory methods to obtain comprehensive data. The findings of this study are expected to provide insight into the impact of each management system on soil physical quality, as well as become the basis for recommendations for more sustainable land management strategies in the future.